Long‐term outcomes of tonsillectomy for recurrent tonsillitis in adults. (25th March 2019) - Tzelnick, Sharon; Hilly, Ohad; Vinker, Shlomo; Bachar, Gideon; Mizrachi, Aviram
Abstract : Background: There is uncertainty regarding the effectiveness of tonsillectomy for recurrent tonsillitis in the adult population. Several studies have described a reduced number and severity of tonsillitis episodes; however, the impact of tonsillectomy on healthcare burden has yet to be studied. The aim of the present study was to evaluate the long‐term outcomes of tonsillectomy in the adult population. Methods: A retrospective review of the central database of Clalit Health Services, Tel Aviv, Israel, between 2003 and 2009 was performed. The study included all adult patients (>18 years) who underwent tonsillectomy due to recurrent tonsillitis. Clinical and epidemiological data from 3 years before and after surgery were collected and analyzed. Results: A total of 3, 701 patients were included in the study. Mean age was 37.4 years, and 42.9% were males. Following surgery, there was a significant decrease in the total number of tonsillitis episodes, otolaryngologist clinic visits, consumption of pertinent antibiotics, and respiratory complaints. Moreover, a reduced number of hospitalizations to the otolaryngology department and shorter hospitalization duration were also noted. Although the total number of hospitalizations was unaffected, there was an increase in the number of primary care office visits. Finally, a break‐even time analysis revealed an average of 2.7 years following tonsillectomy. Conclusion: Tonsillectomy for recurrent tonsillitis is effective in decreasing the number and severity of tonsillitis episodes and might also have an economic benefit. The impact of tonsillectomy on general health needs to be further evaluated; however, it appears that there is no increase in overall morbidity. Level of Evidence: NA Laryngoscope, 130:328–331, 2020